Polish Independent Press Summary, no. 4 (1987) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Tygodnik Mazowsze, no. 220 (16 September 1987). Extract from Z Dnia na Dzień, no. 449 (2 August 1987). Extract from Portowiec, no. 108 (23 August 1987). Extract from Portowiec, no. 109 (12 September 1987). Extract from Robotnik, no. 128 (August 1987). Extract from Serwis Informacyjny Ruchu Wolność i Pokój, no. 45/46 (8 September 1987). Extract from Gazeta Podziemna: "Solidarność" Ziemi Kutnowskiej, no. 6/7 (May/June 1987). Table of Contents from Przegląd Polityczny, no. 9 (1987). Extract from Przegląd Polityczny, no. 9 (1987). Table of Contents from Arka, no. 18 (1987). Extract from Arka, no. 18 (1987). Table of Contents from Wyzwolenie, no. 2(20) (15 June 1987).